On the existence and construction of proper costratifying systems - Mendoza, Octavio (2013)
In this paper we further study the notion of proper costratifying systems, defined in [MPV]. We give sufficient conditions for their existence, and investigate the relation between the stratifying systems defined by K. Erdmann and C. Sáenz in [ES] and the proper costratifying systems.